PENERAPAN BUKU AJAR MICROTEACHING BIOLOGI BERBASIS KOMPETENSI DAN KARAKTER KONSERVASI UNTUK MENGEMBANGKAN KOMPETENSI PERSONAL DAN PROFESIONAL CALON GURU - Sri Sukaesih; Nugroho Edi Kartijono (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Sriwi, 2015)
Abstract: Semarang State University (UNNES) developed curriculum of competence and conservation based. The developing of UNNES 2012 curriculum gave signs for study program to develop its curriculum. Learning equipments of each courses were need to be updated and appropriate with curriculum demand. On 2013 it has developed biology microteaching lesson book based competence and conservation character which was validated by expert, also it was stated proper use. The objective of this research was to describe the effectiveness of biology microteaching book based competence and conservation character application on developing personal competence and professional biology teacher candidate. It was pre-experimental design research by using the one-shot case study plan. It was held to biology microteaching course participant on even semester year 2013/2014. The sample of this research was 46 people. The collected data included book read data, personal and professional teacher competence data. The research result showed that the read book based on colleges gain good and very good criteria. The application of biology microteaching lesson book based competence and conservation character helped the development of teacher candidate personal competence with 82 and 87 percentage or good and very good criteria, while professional teacher competence with 86 and 88 percentage or very good criteria. The conclusion of this research is microteaching lesson book based competence and conservation character has good and very good read also effective on developing biology teacher candidate personal and professional competence. Keywords: microteaching lesson book, competence and conservation character, teacher competence.